Answers to five questions of Shakarim according to the vision of Maulana (Journal of Oriental Studies, 2016)
This article is based on the questions in the field of comparative literature of Shakarim (1858-1931 AD), the Kazakh nation poet, about anthropology and self- Knowledge, according to the vision of Maulana Jalaluddin Rumi. Also the comparison between the perspectives and worldview of Moulana and Shakarim.
Keywords: love; death; perfect man; self-knowledge